KONTRIBUSI MAHASISWA KULIAH KERJA NYATA DALAM MENINGKATKAN KUALITAS PENDIDIKAN SEBAGAI WUJUD PENGABDIAN DI DESA JAHARUN B KECAMATAN GALANG DELI SERDANG-SUMATERA UTARA - Miswar Rangkuti; Ali Safran Pasaribu; Bintang Faiz Ananda; Tika Kesuma Wardani; Sarah Mutia (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
The real work study is a form of student service to the environment and society in order to apply the principles of the tri darma of higher education, namely education, research and community service. Therefore, students carry out KKN in Jaharun B village for 30 days. The implementation of KKN in Jaharun B Village aims to empower the community and develop human resource capacity in the field of education, which is compiled and implemented in several work programs. This article discusses the contribution of North Sumatra State Islamic University students in order to improve the quality of education in Jaharun B Village. There are several work programs carried out by KKN participants, namely Maghrib Mengaji, Tutoring, Teaching in schools, Anti-bullying Socialization and digital literacy and other work programs. This article is a qualitative article with data collection methods, namely interviews and observational studies. The results showed that there was an increase in education in Jaharun B Village which was marked by increased motivation and learning outcomes for village children.